Principle and future trends of indoor positioning in 6G - Xiaoyang WAN; Yaohua SUN; Zeyu WANG (Dianxin kexue)
For supporting location based differentiated services better, 6G has a more stringent requirement on high-precision positioning.Firstly, the principles, characteristics, advantages and disadvantages of the existing indoor positioning techniques were introduced.Then, indoor positioning systems integrating multiple techniques were discussed to overcome the drawbacks of using only a single technique.Moreover, the advances in cooperative positioning systems involving multi-devices and multi-networks were presented with the summary and analysis of centralized and distributed implementation architectures.Finally, the opportunities and challenges faced by 6G indoor positioning were pointed out.